(untitled) (LEARNing Landscapes, 2009)
This article focuses on the need for balance in the educational system and the importance of extracurricular activities to student growth. Using examples from St. George’s School of Montreal, the author shows how balance can be implemented in the curriculum. The article also addresses the different ways St. George’s implements its six main principles into both the curriculum and extracurricular activities.